IN PRAISE OF JAVIER MILEI - Huerta de Soto , Jesús (REVISTA PROCESOS DE MERCADO, 2025)
Today we pay tribute to a man who has no fear, a man who does not hesitate to sacrifice himself in his thirst to change the world. A man whose heart beats strongly at the mere sound of the word “liberty.” For Javier Milei pursues and fights for liberty, his great dream, tirelessly, without compromise, and with an energy and passion that can be found in history only among the great heroes of liberty.